2014
DOI: 10.1177/1440783314528595
|View full text |Cite
|
Sign up to set email alerts
|

‘I just wanted somewhere safe’: Women who are homeless with their children

Abstract: Families are the fastest growing segment of homeless populations in resource-rich countries; most are female-headed. We report on women's experiences of being homeless with their children in Victoria, Australia, emphasising their mental health. Twelve women (who between them had daily responsibility for 31 children) were interviewed, revealing complex pathways into homelessness; the two main contributors were economic decline and domestic violence, with drug use and poor mental health making lesser contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
(34 reference statements)
4
11
0
2
Order By: Relevance
“…Although the shelter system was often seen as a last resort, the well-being of children was an ever-present concern for many parents and a key factor in their deciding to access an emergency shelter. These findings are mostly consistent with those from past research (e.g., Bassuk et al, 1997;Kirkman et al, 2015), demonstrating their relevance and applicability to families in Canada. However, other key findings from the current study are novel additions to the knowledge base on family homelessness.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although the shelter system was often seen as a last resort, the well-being of children was an ever-present concern for many parents and a key factor in their deciding to access an emergency shelter. These findings are mostly consistent with those from past research (e.g., Bassuk et al, 1997;Kirkman et al, 2015), demonstrating their relevance and applicability to families in Canada. However, other key findings from the current study are novel additions to the knowledge base on family homelessness.…”
Section: Discussionsupporting
confidence: 90%
“…In a study of 220 homeless mothers, Browne and Bassuk (1997) found that more than 60% of participants had been physically assaulted by male partners. A small, qualitative study also identified family violence as a key pathway into homelessness that the majority of participants had experienced (Kirkman, Keys, Bodzak, & Turner, 2015). Furthermore, after families exit homelessness, those that experience subsequent partner violence are three times more likely to experience another episode of homelessness in the future (Bassuk, Perloff, & Dawson, 2001).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As noted by Phipps, Dalton, Maxwell, and Cleary (2019), the majority of literature on homelessness focuses primarily on the experiences of men or “homeless people.” However, individuals experiencing homelessness are not a homogenous population, and women experiencing homelessness face unique challenges. Lifetime exposure to trauma, violence, and victimization is a recurring and pervasive concern for women experiencing homelessness (Huey, Broll, Hryniewicz, & Fthenos, 2014; Kirkman, Keys, Bodzak, & Turner, 2015; Osuji & Hirst, 2015; Whitbeck, Armenta, & Welch-Lazoritz, 2015). Likewise, differing complexity and disparities exist for mothers (Phipps et al., 2019).…”
Section: Introductionmentioning
confidence: 99%